Community building for economic empowerment in rural Mozambique: An exploratory study in the Maganja da Costa District - Saide, Eusebio M. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2006.